2017
DOI: 10.1099/jgv.0.000758
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum inhibition of common respiratory RNA viruses by a pyrimidine synthesis inhibitor with involvement of the host antiviral response

Abstract: Our previous screening of 50 240 structurally diverse compounds led to the identification of 39 influenza A virus infection inhibitors (Kao R.Y

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 30 publications
6
69
0
Order By: Relevance
“…Our data are consistent with studies indicating that pyrimidine biosynthesis inhibitors do not cause the expression of IFN when applied alone, and virus growth inhibition by these drugs seems to be independent of IFN-α/β synthesis and the canonical Jak-STAT pathway (Chung et al, 2016; Lucas-Hourani et al, 2013; Lucas-Hourani et al, 2017; Wang et al, 2011; Wang et al, 2016). However, some recent reports show a lack of antiviral effect of DHODH inhibitors in Vero cells, which are deleted for the IFN-α/β gene cluster, suggesting a possible role for secreted IFNs in antiviral activity (Cheung et al, 2017). We found that SW835 activates genes involved in the innate immunity, including ISG56 (interferon-induced protein with tetratricopeptide repeats 1; encoded by IFIT1) and ISG54 (interferon-induced protein with tetratricopeptide repeats 2; encoded by IFIT2), independent of type 1 IFNs or exogenous RNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data are consistent with studies indicating that pyrimidine biosynthesis inhibitors do not cause the expression of IFN when applied alone, and virus growth inhibition by these drugs seems to be independent of IFN-α/β synthesis and the canonical Jak-STAT pathway (Chung et al, 2016; Lucas-Hourani et al, 2013; Lucas-Hourani et al, 2017; Wang et al, 2011; Wang et al, 2016). However, some recent reports show a lack of antiviral effect of DHODH inhibitors in Vero cells, which are deleted for the IFN-α/β gene cluster, suggesting a possible role for secreted IFNs in antiviral activity (Cheung et al, 2017). We found that SW835 activates genes involved in the innate immunity, including ISG56 (interferon-induced protein with tetratricopeptide repeats 1; encoded by IFIT1) and ISG54 (interferon-induced protein with tetratricopeptide repeats 2; encoded by IFIT2), independent of type 1 IFNs or exogenous RNA.…”
Section: Discussionmentioning
confidence: 99%
“…So far attempts to use de novo pyrimidine inhibitors in vivo to control virus infection have met with only partial success (Bonavia et al, 2011; Cheung et al, 2017; Smee et al, 2012; Wang et al, 2011). For example, DHODH inhibitor FA-613 protected 30% of mice from lethal influenza A virus infection (Cheung et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well‐established that cellular pyrimidine metabolism profoundly affects virus propagation. Dihydroorotate dehydrogenase (DHODH), an enzyme catalyzing the fourth step of de novo pyrimidine biosynthesis, was repetitively identified as the cellular target in high‐throughput screening for antivirals conducted by several groups, including us (Hoffmann et al , ; Wang et al , ; Cheung et al , ). Depletion of cellular pyrimidine inhibits the replication of an array of RNA viruses, DNA viruses, and retroviruses.…”
Section: Introductionmentioning
confidence: 99%
“…[107,108] Combined treatments which reduce viral replication and the host immune response to it are likely to be valuable developments. [15] A wide range of repurposed or novel potential antivirals including polymerase, nucleotide synthesis and protease inhibitors and fusion-inhibiting peptides [64,87,[109][110][111][112][113] have been investigated. [87,111] Corticosteroid use is not recommended for acute respiratory distress syndrome.…”
Section: Prevention and Treatmentmentioning
confidence: 99%